Herding Behavior and Decision-Making within the Middle – Class Residential Property Investments - Sofian Arif Susanto; Njo Anastasia (Institute of Research and Community Outreach - Petra Christian University, 2019)
The main purpose of this study is to investigate the causality of the behavioral bias ‘herding’ that was traced down to both social and normative influences. An experimental method was developed to test 125 participants studying finance. The experiment provides a total of 6 houses in which the participants were instructed to appraise to a value that meets their willingness to purchase. The subjects were treated with social and normative influences and their valuation shifts were observed. In total, three valuations were recorded, labeled ‘initial’, ‘social’, and ‘normative’ valuations respectively. Our findings showed that the undergraduates were susceptible to both social and normative influences. However, further analysis showed that some external factors had a role in causing the herding behavior.